VIRTUAL ECONOMY: THE ESSENCE, ADVANTAGES, DISADVANTAGES, AND POSSIBLE LINES OF DEVELOPMENT - О. А. Онищенко; О. В. Обнявко; С. Г. Васильєв (Ринкова економіка: сучасна теорія і практика управління, 2017)
The processes of virtual economy formation both in the world and in Ukraine are presented and analyzed in the article. The approach to the essence of the notion “virtual economy” is studied. The advantages and existing disadvantages of virtual economy are defined. New functions of electronic money are researched. Possible lines of development of the virtualization of the Ukrainian economy are suggested.